TRACKING SUSTAINABLE DEVELOPMENT GOALS (SDGs): IMPORTANCE OF DISEASE REGISTRIES AND BURDEN OF DISEASE IN PAKISTAN - Khan, Ejaz Ahmad (Journal of Ayub Medical College Abbottabad, 2018)
Global Burden of Disease is calculated taking into an account of all the major surveys, hospital records, registries data etc., and this has been highly beneficial in pursuing governments to readdress their health policies ad interventions, and allocate resources according to their local burden of disease. Pakistan’s health system lacks disease registration according to ICD-9 and ICD-10 disease classification. The major hospitals do not have cause of death registered as per these classifications leading to incomparability of these data with global figures. Nonetheless, the statistical disease modelling gives a fair idea of changing disease burden of the societies. In fact, progress towards SDGs for well-certified death registration stands at 0 on a scale of 0-100, for the country during 2016.1 Though the data quality reporting for Pakistan in not very good, and it may be ranked at one star on a five-star-rank, recent estimated morbidity, mortality and disability trends for Pakistan show that Years of Life Lost are higher for neonatal encephalopathy followed by the tuberculosis.2 In South Asia, birth asphyxia and trauma, resulting in to the neonatal encephalopathy, caused DALYs greater than expected in two countries: Nepal and Pakistan with Pakistan showing greater ratio (2.72). Since 1990, People of Pakistan have gained life expectancy at birth from 62.48 (females) and 62.41 (males) to 68.89 (females) and 66.44 (males) in 2016.3 Pakistan is also low on child stunting and child wasting (24 and 15, respectively) in achieving a 100 percent by 2030. Similarly, progress on decreasing under five and neonatal mortalities (27 and 11, respectively) is also quite slow. Universal Health Coverage Index, air pollution, PM 2.5 mortality, WaSH mortality, and child sexual abuse (26, 13, 12, 23 and 0) are the other poor progress areas in achieving SDGs.1 Nonetheless, there have been some improvements and on-time being on the track. For instance, on suicide mortality, alcohols use some improvement on smoking prevalence and conflict mortality. Neurological disorders have dropped since 1990 to 2015 by 18%. However, those estimates came from mix of studies and data needing major evaluation surveys.4,5 Pakistan’s had 30% of its population as adolescents (largest population of adolescents in the EMR region) in 2015: the future of the country. For 10-24 years of adolescents, with the EMR region of WHO, the country is among the highest of the burden of all cause and cause-specific mortality along with the lowest Socio-demographic Index (SDI). This subgroup of population alone suffers from communicable, poor reproductive health, and malnutrition on top of the non-communicable diseases and injuries.6 Another important burden of disease need to be mentioned here is of burden of cardiovascular diseases (CVDs). For the year 2015, this was the highest for Pakistan with 465,116 deaths within the EMR region of WHO compared to the lowest for State of Qatar (117). The DALYs rates for CVDs from 1990 to 2015 went down for all the EMR countries except Pakistan.7 It is imperative that keeping the specific burden of disease for Pakistan under consideration, steps towards robust evidence utilization are taken, and the health systems be redirected addressing those crucial areas supplemented with the local funding, and required human resource so that the country achieves the SDGs well by 2030.